SQUARING THE CIRCLE: TALKING ABOUT ACCESSIBILITY AT DISCOVERY WORLD - (:unkn) unknown (My University, 2023)
In recent years, museums have made a concerted effort to consider accessibility and the needs of the broader community in their programming. This thesis analyzes how Discovery World, a science and technology museum in Milwaukee, Wisconsin, can better accommodate diverse learning styles and disabilities in their 2023 Summer Camp program through a case study of implementation. The thesis analyzes the impact of the plan to improve accessibility and inclusivity in the classroom for children in grades 1-8, focusing on how staff conceptualize the ideal setup and aims to provide valuable insights to enhance inclusivity and accessibility in informal educational settings. To better understand how accessibility and inclusivity in the Discovery World summer camp program influence staff and participants, the study employed participant observation, interviews, and questionnaires. The groups observed in this study were the education team, interns, and support staff. The investigation spans various subtopics, on inclusivity, accessibility, anticipated challenges and opportunities, the effectiveness of Discovery World’s training program, communication dynamics, and expectations regarding teaching styles. By exploring the multifaceted dimensions of interviewees' perspectives, the research contributes to the existing literature on inclusivity and accessibility in informal educational settings. The study acknowledges that staff members envision ideal setups by imagining potential improvements in the program. This stems from the recognition that the quality of training impacts how challenges are perceived and addressed, influencing problem-solving approaches. It highlights the multifaceted nature of these concepts and the importance of shared understanding for consistent implementation. This recognition underscores the paramount importance of cultivating a shared understanding for the sustained and consistent implementation of inclusive and accessible practices within the Discovery World's Summer Camp program.
Keywords: Accessibility; Community; Discovery World; Education; Inclusivity; Summer Camp Program